2021
DOI: 10.1007/s00253-021-11168-3
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the low-calorie sugar substitute 5-ketofructose by different bacteria

Abstract: There is an increasing public awareness about the danger of dietary sugars with respect to their caloric contribution to the diet and the rise of overweight throughout the world. Therefore, low-calorie sugar substitutes are of high interest to replace sugar in foods and beverages. A promising alternative to natural sugars and artificial sweeteners is the fructose derivative 5-keto-D-fructose (5-KF), which is produced by several Gluconobacter species. A prerequisite before 5-KF can be used as a sweetener is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The search for substances that provide a pleasant and sufficient sweetening power without triggering the mentioned side effects led to the discovery of 5-keto- D -fructose (5-KF, 5-ketofructose, 5-oxofructose, 5-dehydro- D -fructose, threo-2,5-hexodiulose), a natural diketone found in honey, white wine, and vinegar in low concentrations ( Burroughs and Sparks, 1973 ; Schiessl et al, 2021 ). This potential sugar substitute can be produced by enzymatic oxidation of D -fructose, a reaction catalyzed by the membrane-bound fructose dehydrogenase complex (FDH SCL ) found in a variety of acetic acid bacteria ( Mowshowitz et al, 1974 ; Ameyama et al, 1981 ; Kawai et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for substances that provide a pleasant and sufficient sweetening power without triggering the mentioned side effects led to the discovery of 5-keto- D -fructose (5-KF, 5-ketofructose, 5-oxofructose, 5-dehydro- D -fructose, threo-2,5-hexodiulose), a natural diketone found in honey, white wine, and vinegar in low concentrations ( Burroughs and Sparks, 1973 ; Schiessl et al, 2021 ). This potential sugar substitute can be produced by enzymatic oxidation of D -fructose, a reaction catalyzed by the membrane-bound fructose dehydrogenase complex (FDH SCL ) found in a variety of acetic acid bacteria ( Mowshowitz et al, 1974 ; Ameyama et al, 1981 ; Kawai et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…This monophosphate was found to be a potent competitive inhibitor of the D -fructose-1-phosphate cleavage catalyzed by liver aldolase ( Englard et al, 1972 ). Concerning microbial degradation, it was demonstrated that 5-KF could not be degraded by 15 members of the most common and abundant intestinal microorganisms ( Schiessl et al, 2021 ). Thus, the sugar derivative seems to be an unsuitable growth substrate for prokaryotes in the human intestine.…”
Section: Introductionmentioning
confidence: 99%
“…As such, 5‐ketofuctose (5‐KF) is an interesting product. It is a naturally occurring compound that has a similar taste and sweetness as fructose (Herweg et al ., 2018 ), but is not metabolized by the human body (Wyrobnik and Wyrobnik, 2006 ) and, as recently shown, not metabolized by 15 prominent bacterial species of the human gut microbiome (Schiessl et al ., 2021 ). 5‐KF therefore meets crucial demands for a new sweetener.…”
Section: Introductionmentioning
confidence: 99%